2003
DOI: 10.1002/app.12618
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and the properties of PMR‐type polyimide composites with aluminum nitride

Abstract: ABSTRACT:A new polyimide composite was developed relying on the concept of in situ polymerization of monomer reactants polyimide. High thermal conductive, low dielectric constant and dielectric loss, and thermal-stable composites were successfully demonstrated by incorporating aluminum nitride powder into the polyimide. The weight percent of aluminum nitride was up to 80%. The thermal and dielectric properties follow the classic composite theories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 29 publications
(32 reference statements)
0
46
0
Order By: Relevance
“…The measurement data of AlN/PI composite were from ref. Wang and Yi (2003). It can be observed from Fig.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…The measurement data of AlN/PI composite were from ref. Wang and Yi (2003). It can be observed from Fig.…”
Section: Resultsmentioning
confidence: 50%
“…As for these structures, the corresponding filler volume percentage is a fixed value at each case, among which the FCC structure possesses the highest one, i.e., 0.7405 (Agari et al 1990). On the other hand, experimental data showed that the volume percentages of fillers can be fairly high, e.g., *65% (Wang and Yi 2003). In order to reflect the close-packed distribution of filler particles, the FCC structure was chosen as the elementary cell in the filler arrangement in the present model, as shown in Fig.1a.…”
Section: Modelingmentioning
confidence: 99%
“…There are also other models to obtain the thermal conductivity, such as the Maxwell-Eucken equation (EMT) (Nielsen 1974), the Nelsen model (Davis and Artz 1995), the effective unit cell model (EUCM) (Ganapathy et al 2005), and the percolation model (Devpura and Phelan 2000). Numerical studies and experimental measurement on the thermal conductivities of the composite materials of different matrix and filler materials (Falat et al 2007a, b;Wang and Yi 2003;Bounenne et al 2005) as well as the filler volume fractions (Agari et al 1990) have also been conducted.…”
Section: Introductionmentioning
confidence: 98%
“…Aluminum nitride exhibits excellent thermal conductivity, good electrical insulation characteristics and a coefficient of thermal expansion closely matching that of silicon in the temperature range of 20-200°C, which make it become a promising substrate and package material [1][2][3]. However, the use of AlN in the micro-electronics industry has been severely constrained because of several inherent impediments.…”
Section: Introductionmentioning
confidence: 99%